Legal Policy on the Replacement of Interim Members of the Asahan Regency Regional Representative Council - M. Irfan Islami Rambe; Dessy Zulfianti Sinaga (Jurnal Ilmiah Wahana Pendidikan, 2026)
Indonesia implements representative democracy, which separates the legislative body into central and regional levels, namely the MPR, DPR, and DPRD. In their role as representatives of the people, council members must be prepared for political demands, both from the parties that nominated them and from the communities they represent. In practice, legislative elections are held through political parties as official participants in general elections. This shows that the existence of a legislative member in a representative institution is not only the result of the people's choice, but also a form of political mandate given by the political party that supports them. Research methods are systematic guidelines used by researchers to collect, analyze, and interpret data in order to answer legal issues that arise. Empirical legal research observes the law in its implementation in society. The results of the study show that the PAW mechanism in Asahan Regency involves good coordination between the DPRD, the Asahan Regency KPU, and political parties. The stages of the PAW procedure are carried out through a process of identifying the reasons for the dismissal of DPRD members, the submission of PAW proposals by political parties, verification of the requirements by the DPRD, technical verification of replacement candidates by the Asahan Regency KPU, and the appointment and inauguration of replacement candidates in a DPRD plenary meeting. Each stage has a clear timeline and requirements in accordance with the provisions of the legislation. The mechanism for determining replacement candidates follows the principle of the next highest number of votes from the same political party in the same electoral district. The most common obstacle is the incompleteness of PAW data and documents that do not meet the requirements set out in the legislation. Administrative obstacles include incomplete required documents and document formats that do not comply with applicable regulations. Timeline and deadline issues become obstacles when there are delays in one of the stages of the process. Human resource constraints, communication and socialization, as well as technological and information system aspects also influence the effectiveness of PAW implementation.